Pelaksanaan Pendaftaran Hak Milik Atas Tanah yang Diperoleh Melalui Pewarisan di Kabupaten Sukoharjo - Febrian, Dede, Darsono, S.H., M.H, Shalman Al Farizy. S.H., M.Kn (2015)
The purpose of this study was to analyze the implementation of the registration of property rights over land, barriers, and solutions taken on the implementation of the registration of property rights over land acquired through inheritance in Sukoharjo. This research includes empirical juridical namely discussing the implementation and examine the implementation of legal provisions in practice. Research conducted Sukoharjo jurisdiction. Data were analyzed using qualitative analysis. The results showed that: First, the implementation of the registration of property rights over land acquired through inheritance is performed by the receiving rights to land as an inheritance to the land office to bring documents such as certificate of rights is concerned, the death certificate the person whose name is recorded as holders of rights and a letter of proof as heir. Second, obstacles emerged was the lack of human resources (personnel) who carry out the certification and the volume of work increases. External barriers outline: the public does not know the procedure of certifying, the cost of expensive land registration, and inheritance rights disputes.